One and one is not two: taking a fresh look at membrane interfaces. Issue 12 (December 2018) - Belardi, Brian; Fletcher, Daniel
Abstract Plasma membranes sit at the divide — conceptually and literally — between the interior and exterior milieu of cells, coordinating communication between nearby cells and structuring surrounding tissue. While great effort over the past half-century has advanced our understanding of the molecular organization of the plasma membrane, much of this work has focused on free plasma membranes that are not in contact with other cells. Recent studies have highlighted unique and unexpected features of membrane interfaces formed between two cells, where the physical and chemical constraints of the interface conspire to create a system that is distinct from either plasma membrane alone. Inspired by this emerging view of cell–cell contacts, we propose classifying interfaces between cells as a distinct cellular compartment. Dan Fletcher's lab comments on the unique properties of membranes at cell–cell adhesions, suggesting that cell–cell interfaces are a separate cellular compartment.